Identifikasi pola ruang dan perubahan fungsi ruang Puri Pemecutan Denpasar - Pratama, A.A.Ngurah Ari Putra; Yusiana, Lury Sevita; Astiningsih, A.A. Made (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018, 2018)
Identification on spatial patterns and changes of Pemecutan Castle Denpasar. Puri Pemecutan is one of royal palaces (puri) in Denpasar city which has a very high historical value. The puri has a different spatial pattern compared to traditional Balinese house in general. The magnitude of royal palaces family needs of residence and the number of activities carried out by the puri's family caused a change of pattern and function of each space in Puri Pemecutan. The aims of this study is to identify spatial patterns and functions of the Puri Pemecutan in 1942 and 2016, and identify changes in spatial patterns and functions that occur in Puri Pemecutan. The research method used was survey with data collection is observation, interview, and study leterature by descriptive qualitative method. The step of this research starts from the inventory, analysis, synthesis, and recommendation. The result of this research showed that the pattern of space and space function were change of the Puri Pemecutan in 1942 and year 2016. The study also give recommendations of spatial puri based on changes of space function change of the Puri Pemecutan.